British Primitives: W.R. Lethaby at the Borders of Antiquarianism and Art History in the Early Twentieth Century. (2nd April 2016) - Snape, Julia
Abstract : This paper examines how English medieval painting became the focus of a new kind of scholarly scrutiny, through the analysis of a series of articles written by W.R. Lethaby (1857–1931) for The Burlington Magazine between 1916 and 1918. Lethaby's writings are interpreted here as an exercise intended to re-position English medieval painting as a subject worthy of connoisseurial attention. Contemporary exhibitionary practice was also crucial in illustrating the new status of English medieval painting and in defining its English character. The exhibition British Primitives, held at the Royal Academy in 1923, is examined here to evaluate how this re-presenting of medieval art to reflect contemporary scholarship also made it vulnerable to contemporary modes of consumption, as witnessed in the increased value (both cultural and monetary) of medieval art on the international art market.